Structure development of Thailands kaolin by mechanochemical technique - W. Tanwongwan; T. Wongkitikun; K. Onpecht; S. Srilai; S. Assabumrungrat; N. Chollacoop; A. Eiad-ua (My University, 2020)
Metakaolin was known as high potential starting material for zeolite production by it was obtained by the calcination process of kaolin. However, contaminants such as muscovite were still found in the structure of metakaolin. The mechanochemical technique has been applied for the development of metakaolin structure after the calcination process by kaolin from Lampang province in Thailand was chosen as a starting material. Important factors include rotation speeds (300-500 rpm) and weight ratios of grinding balls per metakaolin (4:1, 8:1, 12:1, and 16:1) were studied in this research. The result from many characterization techniques includes X-ray diffraction, Raman spectroscopy, Particle size analysis, and Scanning electron microscopy was demonstrated that contaminants of metakaolin, relative crystallinity, crystallite size, and particle size have a tendency to decreased with increasing of rotation speed and a weight ratio of grinding balls per metakaolin. The most effective condition for the structure development of metakaolin is using the weight ratio of grinding balls per metakaolin at 16:1 and 500 rpm speed. The structure of metakaolin was changed to silica-rich phases with the lowest crystallization, the smallest crystallite size, the smallest particle size, and the structure of muscovite was completely destroyed which these properties are good for application of metakaolin for the synthesis of zeolite.
Keywords: Metakaolin; Muscovite; Zeolite Catalysis and Synthesis